The Influence of Capital Adequacy Ratio (CAR), Non-Performing Loans (NPL), Return on Assets (ROA), and Loan To Deposit Ratio (LDR) on Financial Sustainability in Regionally Owned Enterprises (BUMD) Bank Pasar Kulon Progo for the 2018-2023 Period - Eva Farida Kristin Wijayanti; Bangun Putra Prasetya (Journal Of Management Analytical and Solution (JoMAS), 2024)
Bank Pasar Kulon Progo plays a key role in promoting regional economic growthand improving welfare. To maintain financial stability, it is essential to assessfactors influencing financial sustainability. This study examines the impact ofCapital Adequacy Ratio (CAR), Non-Performing Loans (NPL), Return on Assets(ROA), and Loan to Deposit Ratio (LDR) on the Financial Sustainability Ratio(FSR) of Bank Pasar Kulon Progo from 2018 to 2023. A quantitative approachwas used, analyzing financial report data with purposive sampling. Multiplelinear regression was applied to assess the relationships between the variables.The results show that CAR, NPL, ROA, and LDR have a significant impact onFSR, collectively explaining 79.5% of its variation (RÂ² = 0.795). The remaining20.5% is influenced by other factors outside the model. These findings suggestthat effective management of CAR, NPL, ROA, and LDR is crucial for ensuringthe financial sustainability of Bank Pasar Kulon Progo.